Pluviometric and fluviometric trends in association with future projections in areas of conflict for water use. (1st October 2020) - Silva, Felipe Bernardes; Almeida, Laura Thebit de; Vieira, Edson de Oliveira; Silva, Demetrius David da; Maciel, Isabela Piccolo; Parma Júnior, Fernando
Abstract: Rapid population growth coupled with climate change has been putting pressure on natural resources worldwide, especially on water resources. The Paracatu basin located in Brazil is a basin which has been showing a reduction in its water availability for many years due to the growing demand for irrigation in the region. Therefore, the objective of the present work was to analyze the trends in the flow and precipitation data for the Paracatu basin and correlate them with land use between the years 1980 and 2019, and thus make a projection of flows through the year 2030 based on these results. The projections of future flows in the fluviometric stations analyzed were obtained using the WEAP model, considering the projected increase in the irrigated area for the region and the future climate data from the IPCC for the RCP 4.5 scenario. The results of the analyzes indicated a tendency towards a reduction in flows in all the analyzed fluviometric stations, both in the monthly and annual series, whereas the total annual precipitation did not show a trend in the analyzed period. Future flows showed a downward trend, as well as flows observed in the period from 1980 to 2019, reinforcing that activities such as irrigated agriculture without planning can negatively affect the sustainability of water resources, intensifying conflicts and tensions which already exist in the basin. This type of analysis proved to have great potential to contribute to the solution of water resource management challenges in several hydrographic basins around the world which are in a situation of scarcity and conflict. Highlights: The seasonality in the precipitations were not determinant in the flow data trends There was a tendency to reduce the annual minimum flow in all fluviometric stations Behavior of the stream flows are associated with the increased demand for water use Future flows showed a downward trend, as well as flows observed This method has great potential to the solution of water resource management